KALATIDHA KARYA SENO GUMIRA AJIDARMA: SEBUAH POTRET BURAM KEMANUSIAAN - Maryanah, Imas (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2013)
AbstractThe changing dynamic of human lives makes most of them ignorant to the values of right and wrong. Truth, freedom, and justice have become scarce and beyond real.Cruelty has caused fear, restlessness, and misery. In order to be free from excruciatingpressure, Kalatidha describes a picture of how someone has lived in his dream happily.The dreams and goals he is been longing for are only enjoyed in that surreal world, theworld freed from norms, ideas, and public opinion. â€œRunning awayâ€ is the word used todescribe how people lock themselves away from the real world. Â For him, the real world he understands is the world that can give him joy,happiness, and cheerfulness. Things that are immoral in the eyes of the public are noshame to him. One thing he is sure of, that life is a journey, and how he live it. Emptinessis no longer misery, but a process that has to be passed through the journey. Kalatidhahas become a picture of how inner unrest becomes a focus of deceitful real life pantings.Deceit and dishonesty are stupid, and craziness is an act of hopelessness. Â Key words : Dream, Journey, Deceit AbstrakDinamika gambaran kehidupan manusia yang terus-menerus berubah menyebabkan sebagian manusia tidak mengindahkan lagi, mana yang harus dilakukanmana yang dilarang. Kebenaran, kebebasan, keadilan menjadi barang langka yanghanya menjadi impian belaka. Kekejaman telah memunculkan ketakutan, kegelisahan,kesengsaraan. Agar terbebas dari tekanan yang menyiksa, Kalatidha menyajikan sebuahpotret bagaimana seseorang telah hidup di alam khayalnya dengan bahagia. Impian dancita-cita yang selama ini didambakan, hanya dapat dinikmati di alam â€œsanaâ€. AlamyangÂ terbebas dari norma, ide, pendapat masyarakat. â€œLariâ€ itulah kata yang tepatuntuk menggambarkan bagaimana seseorang telah memenjarakan dirinya darikehidupan nyata. Â Kehidupan nyata yang ia pahami hanyalah dunia yang dapat memberinyakesenangan, kegembiraan dan keceriaan. Hal-hal aneh yang dianggap menyimpang olehmasyarakat pada umumnya bukan merupakan celaan baginya. Satu hal yang ia yakinibahwa hidup ini adalah sebuah perjalanan, dan bagaimana ia menjalankannya. Kekosongan dan kehampaan bukan lagi siksaan, tapi sebuah proses yang harus dilewatidalam menempuh perjalanan. Kalatidha telah menjadi sebuah potret bagaimanapergolakan batin menjadi fokus sebuah lukisan kenyataan semu. Kepalsuan dan kepurapuraanadalahhalbodoh,dankegilaanadalahtindakandarisuatukeputusasaan.Key words : Impian, Perjalanan, Semu